Effect of enhanced oxygen reduction activity on oxygen permeation of La0.6Sr0.4Co0.2Fe0.8O3−δ membrane decorated by K2NiF4-type oxide - Han, N.; Zhang, S.; Meng, X.; Yang, N.; Meng, B.; Tan, X.; Liu, Shaomin (2016)
Asymmetric dense La0.6Sr0.4Co0.2Fe0.8O3−δ hollow fiber membranes were prepared by the joint phase inversion and sintering processes. Surface treatment by hydrochloric acid-etching and decoration of dispersed porous (La0.5Sr0.5)2CoO4+δ thin layer, was applied to improve the surface exchange reaction kinetics of oxygen reduction. Oxygen permeation performance of the unmodified and modified membranes was investigated under different operating conditions. Experimental results indicate that both surface treatment strategies effectively accelerate the oxygen permeation rate of the resultant membranes by the improved surface exchange kinetics; in particular, the oxygen fluxes were enlarged from 0.036 to 1.021 ml min−1 cm−2 of the bare membrane to 0.201–1.311 ml min−1 cm−2 of the decorated membrane by (La0.5Sr0.5)2CoO4+δ with a minimum improvement percentage of 28% when operation temperature varied from 700 to 1000 °C with helium flow rate of 150 ml min−1. Furthermore, better flux enhancement of the surface-modified membrane was observed at lower temperature regimes than at higher temperatures indicates at lower temperatures the surface exchange reaction kinetics play a larger role in controlling the overall oxygen transport through the membrane; in other words, the relative limiting effect of the ionic bulk diffusion becomes more noticeable at higher temperatures. In addition to the significant oxygen flux improvement, the surface decorated membrane also displays high permeation stability under the investigated operating conditions.